Stadium Games : Fifty Years of Big League Greed and Bush League Boondoggles - Weiner, Jay, 1954- (Book collections on Project MUSE., 2000)
In Stadium Games, veteran Minneapolis Star Tribune reporter Jay Weiner analyzes Minnesota's fifty-year history with pro sports and the issues contributing to the bid for a new stadium for the Minnesota Twins, along the way providing a big-picture evaluation of national sports economics.